Studying strands polarity of different viroids and their combinations in infected hop plants - Andrej SEČNIK; Sebastjan RADIŠEK; Nataša ŠTAJNER; Jernej JAKŠE (Acta Agriculturae Slovenica)
Hop plant (Humulus lupulus L.) is an important industrial crop, grown for harvesting hop cones however, it is a host to four different viroids as well. The nature of viroid infections is not entirely clarified. In our work, we focused on analyzing viroid accumulation and their strands polarity through RNA sequencing and reverse transcription polymerase chain reaction in real time. RNA-seq data indicate that viroids amplify until saturation further demonstrating plant's biological capacity. Negative fold changes in accumulation of individual viroids between hop samples with single and multiple infections are suggesting an antagonistic relationship amongst viroids, where citrus bark cracking viroid seems to be the least and hop stunt viroid the most sensitive to the other two. RNA-seq data also show that on average (−) viroid strand is dominating over (+), especially for the citrus bark cracking viroid. Reverse transcription polymerase chain reaction in real time results from strand polarity analysis seem to be less consistent between different combinations of infection but are showing level of conformity with RNA-seq in the case of citrus bark cracking viroid.